The European Alps – an exceptional range of mountains? Braudel's argument put to the test. Issue 1 (2nd January 2017) - Mathieu, Jon
Abstract: In his classic work about the Mediterranean in the period of Philipp II, French historian Fernand Braudel designates the European Alps an 'exceptional range of mountains' and offers several reasons therefor. In contrast to other parts of Braudel's work, this argument has gone largely unnoticed in scholarship. This article intends to put it to the test in light of recent publications on the Alps. The first two sections give an outline of Braudel's dealings with mountain regions and of historical research on the Alps from the 1970s onwards. The third section comments on the suitability of Braudel's criteria for empirical assessments in a comparative perspective. In the conclusions it is argued that Braudel's general intuition is still valid to some degree. It is less certain, however, that all the criteria are pertinent. More importantly, the findings emphasize the fact that the history of the Alps cannot be studied without paying close attention to their links with the surrounding lowlands. Thus the question of alpine exceptionality raises the question of the special trajectory of these lowland regions within the larger history of Europe.